Gender Differences in Climate Change Perception and Adaptation Strategies: The Case of Three Provinces in Vietnam’s Mekong River Delta - McKinley J; Adaro, C.; Pede, Valerien O.; Rutsaert P; Setiyono T; Cong Tran Thanh; Lien Huong D; Trung Kien N; Balangue, Z.; Bandyopadhyay, S.; Sheinkman, Michael; Wassmann, Reiner (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
The Policy Information and Response Platform on Climate Change and Rice in ASEAN and its Member Countries Project (PIRCCA) is one of the trial projects funded under Flagship 4. PIRCCA has an overarching goal to enable policymakers in ASEAN countries to make informed decisions on (1) food security policies focusing on the supply and availability of rice, (2) climate change adaptation policies, and (3) gender action plans.